Incidence of glenohumeral instability in collegiate athletics - Owens, B. D.; Agel, J.; Mountcastle, S. B.; Cameron, K. L.; Nelson, B. J. (The American Journal of Sports Medicine, 2009)
Glenohumeral instability is a common injury sustained by young athletes. Surprisingly, little is known regarding the incidence of glenohumeral instability in collegiate athletes or the relevant risk factors for injury. A better understanding of the populations most at risk may be used to develop preventive strategies.